Kemijski dejavniki tveganja v prehrani - Šostar Turk, Sonja; Rozman, Urška; Blaznik, Urška; Viher Hrženjak, Vesna; Golja, Viviana; Mivšek Mušič, Ema; Nahtigal, Blaža; Perharič, Lucija; Pajnkihar, Majda; Vrbnjak, Dominika (2022)
Chemical Risk Factors in Nutrition. Food is chemically the most complex part of the environment to which humans are exposed on a daily basis. Food consists of chemical ingredients that give it nutritional value, such as proteins, fats, carbohydrates, water, fiber, vitamins and minerals, and other chemical ingredients that give it flavour and colour. Chemical contaminants, natural toxins and additives that pass into food throughout the food chain from growth, processing, preparation and storage of food also occur in food. There are many sources and pathways for chemical contaminants to enter food, some of which are intentionally added to food and others pass into food unintentionally as a result of human activity. Food safety is a fundamental public health concern. The textbook collects and presents the most common chemical contaminants in the human nutrition, as well as related legislation and health risks.
Keywords: safe food; toxic elements; persistent organic pollutants; mycotoxins; plant toxins; pesticides; additives; medicines; acrylamide; trans fats; nitrogen compounds; polyaromatic hydrocarbons; allergens, chemical endocrine disruptors; nanotechnology